Drugs for the eye: drops or ointments?. Issue 14 (6th July 1973) - Unknown
Abstract : Many ophthalmic preparations are available both as drops and as ointment but the advantages of one formulation over the other in the treatment of a particular condition have rarely been defined. Recent work on the mechanisms underlying the development of a normal stable precorneal tear film has shown that a particular combination of mucus and tears is required to produce the necessary hydrophilic surface on the cornea which will wet evenly and remain wetted, 1 and ideally topical drugs should not impair the integrity of this film.